An assessment of RNA content in Prymnesium parvum, Prymnesium polylepis, cf. Chattonella sp. and Karlodinium veneficum under varying environmental conditions for calibrating an RNA microarray for species detection. Issue 1 (3rd February 2014) - McCoy, Gary R.; Kegel, Jessica U.; Touzet, Nicolas; Fleming, Gerard T.A.; Medlin, Linda K.; Raine, Robin
Abstract Traditional methods of identification and enumeration can be somewhat ambiguous when identifying phytoplankton that requires electron microscopic examination to verify specific morphological features. Members of the genus Prymnesium (division Haptophyta), members of the Raphidophyceae and naked dinoflagellates are examples of such phytoplankton whose identification can be difficult. One alternative to traditional microscopy‐based methods of identification is to use molecular protocols to detect target species. Methods that measure cellular DNA and RNA content can be used to estimate the number of cells present in a sample. This study investigated the variation of RNA yields in Prymnesium parvum, P. polylepis, cf. Chattonella sp. and Karlodinium veneficum cells grown under different light, temperature, salinity and inorganic nutrient conditions. This information was used to calibrate the signal intensity of a variety of oligonucleotide probes spotted onto the microarrays for the detection of toxic algae (MIDTAL), which is being developed to aid national monitoring agencies and to provide a faster means of identifying and quantifying harmful phytoplankton in water column samples.